Developing a knowledge management strategy for the public sector. - Chia, Li Theng. (2008)
This report seeks to identify a knowledge management strategy that may be adopted by public organisations, based on literature review and qualitative analysis. The proposed strategy comprises five main elements: Organisation Culture, People Development, Organisation Structure, Reward Structure and Knowledge Stewardship, which are instrumental in the development of organisations.